PERANCANGAN SISTEM PENDETEKSI ASAP PADA RUANGAN PERPUSTAKAAN MENGGUNAKAN SENSOR MQ-2 DAN TAMPILAN LCD DENGAN MIKROKONTROLER ATMEGA32 - Ruri Hartika Zain; Sahari Sahari; Elmi Rahmawati (Jurnal Teknologi Informasi dan Pendidikan, 2016)
The smoke can cause so much harm , one of which material losses and damages in the form of air pollution . Smoke can be caused by many things , one of which is the smoke that causes the malfunction by short-circuit ( surge Electrical ) . Electrical surge can cause sparks which would later appear the smoke from the fire spark . If this is not addressed at a rapid pace will most likely occur in a library room air pollution by smoke or fire in the room will berdampaknya library